Identification of Nine Compounds known as “Smart Drugs” in Japan from 2020 to 2022 - R. Tanaka; M. Kawamura; S. Mizutani; R. Kikura-Hanajiri (Emerging Trends in Drugs, Addictions, and Health)
Introduction: In recent years, several compounds known as “smart drugs”, also known as “nootropics”, have been detected in Japan. The smart drugs have been claiming to enhancing human brain activity. In this study, nine compounds known as “smart drugs” were isolated and identified from the products sold as reagents or supplements. Methods: Six powdery products and three capsule products were obtained on the internet in Japan between April 2020 and June 2022. They were analyzed by LC-PDA-MS and GC-MS, and compounds detected in the products were identified by direct comparison with data of analytical standards or performed by NMR (1H-NMR, 13C-NMR, HMQC, HMBC, H-H COSY). Results: Two of these substances were identified as Phenylpiracetam and Phenylpiracetam hydrazide by the LC-QTOF-MS and NMR. The other seven unknown substances were identified as IDRA-21, Bromantane, Sunfiram, 9-MBC, Fasoracetam, CE-123, and GTS-21 by comparing the data with those of the authentic substances. Phenylpiracetam and Phenylpiracetam hydrazide are analogs of piracetam, which is used to treat memory impairment in Alzheimer's disease, stroke, and Parkinson's disease. CE-123 is an analog of modafinil, a psychostimulant, used for the treatment of narcolepsy. Conclusions: Some of the compounds detected in this study are analogs of pharmaceuticals or compounds synthesized for drug development. Since these pharmaceuticals have pharmacological effects on central nervous system, an excessive intake of these analogs may cause health problems.